Automation and electrical control of a mortising machine with 12 synchronous perforations in the manufacture of stairs - Daniel López-Borjas; Omar Chamorro-Atalaya; Florcita Aldana-Trejo; Vidalina Chaccara-Contreras; Nestor Alvarado-Bravo; Erika Zevallos-Vera; Evelyn Anicama-Navarrete (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
With the constant technological development, industries have been incorporating technologies into their manufacturing processes, which generate benefits in the productive field. In the manufacturing process of wooden stairs, the faults of the products, generates that an adequate homogeneity is not achieved, often because the manual operation is carried out without having established parameters in the handling of the mortiser. In this sense, the present article develops an automatism and electrical control of a 12 synchronous perforation mortiser, in order to improve the productivity of the perforation stage in the manufacture of wooden stairs. As part of the development, the electrical, pneumatic and mechanical control system is carried out using Autodesk Inventor software, while the KOP programming is carried out in Tía Portal V14 with connection to S7 PLCSIM V14 using the programmable logic controller (PLC) 1214C. Once the automation has been implemented, a reduction in the processing time per wooden strip of 74.68% is obtained. Likewise, with the automatic process, it is possible to produce 2,460 units of slats, that is, the monthly production increases by 294.9%, in other words, the productivity is 58 units of slats manufactured per hour.